EMPATHY OVER RETRIBUTION: EXAMINING THE ROLE OF RESTORATIVE JUSTICE IN DOMESTIC VIOLENCE CASES - Nilakshi; Reeta; Rathi, Monika (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Restorative justice has emerged as an alternative paradigm in recent years that provides a unique approach to addressing harm within the criminal justice system. Restorative justice endeavours to rectify the damage caused by an offense by emphasizing accountability, empathy, and healing, rather than concentrating solely on punishment. Restorative justice offers a framework in which victims of domestic violence can express their experiences, receive validation, and actively engage in a process that aims to recognize and alleviate their trauma. In turn, offenders are encouraged to confront the consequences of their actions, accept responsibility, and participate in efforts to make restitution. This restorative approach is predicated on the notion that a process that fosters mutual comprehension and healing, rather than retribution, can be advantageous to both victims and offenders.